Ketamine reduceslethality on the acute arnmonia intoxication in mice - Boscán, Pedro; Piña Crespo, Juan; Dalb, Nelson (Investigación Clínica, 2013)
Injection of large doses of ammonia (1.2 g/kg, i.p.) was used to induce acute toxicity in mice which was characteritzed by hyperresponsiveness, taquipnea, clonic and tonic seizures and death. Pretreatment with 20. 40. or 80 mg/Kg. i.p., of ketamine increased 30 to 55% survival rate. This pretreatment significantly retarded the beginning of the first tonic convulsion attenuating its intensity and delayed the time of the animal death: but did not alter the onset of the first clonic seizures. These experiments may be an evidence that support the hypothesis that seizures due to hyperammonemia involve activation of excitatory amino acid receptors.